2001
DOI: 10.1021/jm010212m
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Effects of Structural Variation at the Meta Position of the Aromatic Rings and at the End of the Alkenyl Chain in the Alkenyldiarylmethane Series of Non-Nucleoside Reverse Transcriptase Inhibitors

Abstract: In an effort to elucidate a set of structure-activity relationships in the alkenyldiarylmethane (ADAM) series of non-nucleoside reverse transcriptase inhibitors, a number of modifications were made at two locations: (1) the meta positions of the two aromatic rings and (2) the end of the alkenyl chain. Forty-two new ADAMs were synthesized and evaluated for inhibition of the cytopathic effect of HIV-1(RF) in CEM-SS cell culture and for inhibition of HIV-1 reverse transcriptase. The size of the aromatic substitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 49 publications
4
36
0
Order By: Relevance
“…9 However, an attempted synthesis of 3-but-3-ynyl-1,3-oxazolidin-2-one (25) from 3-butyn-1-bromide or 3-butyn-1-iodide and 2-oxazolidinone failed due to an elimination reaction. In order to minimize the competitive elimination reaction, the halide leaving group was changed to a tosylate, which favors nucleophilic substitution over elimination when a competition between S N 2 and E2 processes is involved.…”
Section: Chemistrymentioning
confidence: 99%
“…9 However, an attempted synthesis of 3-but-3-ynyl-1,3-oxazolidin-2-one (25) from 3-butyn-1-bromide or 3-butyn-1-iodide and 2-oxazolidinone failed due to an elimination reaction. In order to minimize the competitive elimination reaction, the halide leaving group was changed to a tosylate, which favors nucleophilic substitution over elimination when a competition between S N 2 and E2 processes is involved.…”
Section: Chemistrymentioning
confidence: 99%
“…They resemble substructures of the published NNRTIs 26 and 27 ( Figure 9). 21,25 Another way to investigate if fragments similar to known NNRTIs are more prone to bind to HIV-1 RT than dissimilar fragments is to create an enrichment plot based on the maximum Tversky similarity. This is done by first sorting the screened fragment library on the basis of maximum Tversky similarity, then plotting the cumulative percent of all hits recovered vs percent of library screened.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of nonbinding fragments(21)(22)(23)(24)(25) representing substructures of published NNRTIs(3,(18)(19)(20) [22][23][24]. Compound 3 is delavirdine, one of the reference compounds used.…”
mentioning
confidence: 99%
“…20,22,23 Previous molecular modeling studies with ADAM 1 have indicated the possibility for either bifurcated hydrogen bonding between the side chain ester carbonyl of the ligand, the terminal amino group of Lys103, and the backbone amide N-H of Lys101 22 or hydrogen bonding to the backbone amide N-H of Lys101 only. 23 In the present case, the model displays a hydrogen bond from the side-chain ester carbonyl and Lys103 only, and this may result from displacement of the side chain more in the direction of Lys103 resulting from the larger steric bulk of a thioester group in 23 versus an ester group in 1. However, the general features of the model derived from 23 are similar to those seen with 1, and the two have the general "butterfly shape" seen in the X-ray crystal structures of nevirapine and a number of other NNRTIs.…”
Section: Biological Results and Discussionmentioning
confidence: 99%